Disturbance Increases Microbial Community Diversity and Production in Marine Sediments - Galand, Pierre E.; Lucas, Sabrina; Fagervold, Sonja K.; Peru, Erwan; Pruski, Audrey M.; Vétion, Gilles; Dupuy, Christine; Guizien, Katell (Frontiers in Microbiology, 2016)
Disturbance strongly impacts patterns of community diversity, yet the shape of the diversity-disturbance relationship remains a matter of debate. The topic has been of interest in theoretical ecology for decades as it has practical implications for the understanding of ecosystem services in nature. One of these processes is the remineralization of organic matter by microorganisms in coastal marine sediments, which are periodically impacted by disturbances across the sediment-water interface. Here we set up an experiment to test the hypothesis that disturbance impacts microbial diversity and function during the anaerobic degradation of organic matter in coastal sediments. We show that during the first 3 weeks of the experiment, disturbance increased both microbial production, derived from the increase in microbial abundance, and diversity of the active fraction of the community. Both community diversity and phylogenetic diversity increased, which suggests that disturbance promoted the cohabitation of ecologically different microorganisms. Metagenome analysis also showed that disturbance increased the relative abundance of genes diagnostic of metabolism associated with the sequential anaerobic degradation of organic matter. However, community composition was not impacted in a systematic way and changed over time. In nature, we can hypothesize that moderate storm disturbances, which impact coastal sediments, promote diverse and productive communities. These events, rather than altering the decomposition of organic matter, increase the substrate turnover and, ultimately, remineralization rates.